THE ROLE OF AUDIT COMMITTEE ATTRIBUTES IN ENHANCING OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE STANDARDS - Cahyani, Ni Made Ari; Redita, Ketut; Rinaningsih, Rinaningsih (Universitas Riau, 2024)
This research aims to evaluate how the characteristics of the audit committee contribute to the enhancement of environmental, social, and governance (ESG) reporting standards. The audit committee's contribution is assessed through financial acumen, scope, autonomy, and the regularity of its meetings. This study does not only focus on certain industries but all industries with ESG scores that are routinely assessed by Bloomberg for the 2017-2021 period in Indonesia except the financial industry. The sample comprises of 67 companies, so that the total observations used are 335 firm-years with fixed effect model data panel analysis. The findings imply that the independence of the audit committee's independence has a notably positive impact on the quality of ESG disclosures. Meanwhile, the frequency of audit committee meetings has a notably negative impact on the quality of ESG disclosures. However, financial expertise and the size of audit committee do not correlate to the quality of ESG disclosures. The sensitivity analysis supports the entire result of the hypothesis test. Sensitivity tests were carried out on each of the ESG components, namely Environmental, Social and Governance.